2014
DOI: 10.1155/2014/985149
|View full text |Cite
|
Sign up to set email alerts
|

The Technical Efficiency of Specialised Milk Farms: A Regional View

Abstract: The aim of the article is to evaluate production efficiency and its determinants of specialised dairy farming among the EU regions. In the most of European regions, there is a relatively high significance of small specialised farms including dairy farms. The DEAVRS method (data envelopment analysis with variable returns to scale) reveals efficient and inefficient regions including the scale efficiency. In the next step, the two-sample t-test determines differences of economic and structural indicators between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
(26 reference statements)
2
25
0
2
Order By: Relevance
“…It means that the size of farms does not significantly affect the efficiency improvement. Alternatively, the size of farm is a significant determinant of the static technical efficiency -the fully efficient regions are significantly higher than the inefficient ones (Špička and Smutka 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that the size of farms does not significantly affect the efficiency improvement. Alternatively, the size of farm is a significant determinant of the static technical efficiency -the fully efficient regions are significantly higher than the inefficient ones (Špička and Smutka 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Farms with the specialized milk production do not have the same significance across the EU. Špička and Smutka (2014) found out that the share of milk production in the specialised dairy farms within the total milk production in the EU ranges from one quarter (Czech Republic) to just under 100% (some regions in Spain and Portugal). Based on the regional view, they also revealed that the significant economic determinants of the production efficiency in the specialised dairy farming are the farm size, herd size, crop output per hectare, the productivity of energy, and capital (at a = 0.01).…”
Section: Doi: 1017221/112/2014-agriceconmentioning
confidence: 99%
“…The performance of Czech dairy farms has been analysed in only a few studies (see Foltýn et al 2009;Frelich et al 2011;Perný and Kubíčková 2011;Doucha et al 2012;Čechura et al 2014;Špička and Smutka 2014) and these studies usually measured the performance physically by the total factor productivity and technical efficiency. Kumbhakar and Lien (2009) pointed out that the maximization of productivity growth might not correspond with the profit maximization that is the goal of most producers.…”
mentioning
confidence: 99%
“…However, the operationalization of linkages between soil management, soil functions, and ecosystem services remains a challenge (Schwilch et al, 2016;Stavi et al, 2016). Our framework addresses this gap by linking soil management practices to soil functions and services in particular (Figure 1 Gomes et al, 2009;Hoang, 2011;Hoang & Alauddin, 2012;Lee & Park, 2017;Masuda, 2016;Pagotto & Halog, 2016;Sabiha, Salim, & Rahman, 2017;Spicka, 2014;Spicka & Smutka, 2014;Wang, Chen, Wu, & Li, 2015Boshrabadi et al, 2008Li et al, 2013 Note. Separate indicators are determined by the fraction of benefit divided by resource.…”
Section: Ecosystem Services Impactsmentioning
confidence: 99%